2015
DOI: 10.1515/pac-2015-0404
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical, electrochemical, and spectroelectrochemical investigation of electronicpush–pullbenzothiadiazole fluorophores

Abstract: Two electronic push-pull fluorophores consisting of a benzothiadiazole core and a terminal N,N-dimethylamino electron donating group were prepared. The effect of the terminal electron withdrawing group (-NO 2 and -CN) on the spectroscopic, electrochemical, and spectroelectrochemical properties were examined. The fluorophores were solvatochromic with Stokes shifts upward of 9000 cm −1 being observed in aprotic solvents of varying polarity. It was found that the fluorophores fluoresced appreciably (86 % > Φ fl >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Skene et al reported two push-pull N,N -dimethylamino-benzothiadiazole fluorophores, M11a and M11b , which were found to exhibit solvochchromism, electrochromic and electrofluorochromic properties [29]. Thin film of M11a with a terminal cyano group changed visible colour from yellow to mauve upon oxidation, with fluorescence colour correspondingly changing from purple to blue.…”
Section: Organic Small Elc Moleculesmentioning
confidence: 99%
“…Skene et al reported two push-pull N,N -dimethylamino-benzothiadiazole fluorophores, M11a and M11b , which were found to exhibit solvochchromism, electrochromic and electrofluorochromic properties [29]. Thin film of M11a with a terminal cyano group changed visible colour from yellow to mauve upon oxidation, with fluorescence colour correspondingly changing from purple to blue.…”
Section: Organic Small Elc Moleculesmentioning
confidence: 99%
“…Besides inorganic thin layers, organic and metal-organic compounds can also exhibit electrochromism. These compounds are, e.g., small molecules like benzothiadiazole fluorophores, bipyridylium salts (also called viologens), and electrically conductive polymers like derivatives of polyaniline (PAni) and polythiophene (PT) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These polymers exist in a broad variety of oxidation states, which all appear in a different color, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2 Very interesting are compounds exhibiting socalled multielectrochromism: various low redox states derived from distinct absorption bands at different wavelengths. Inorganic metal oxides, [3][4][5] organic conjugated polymers [6][7][8] or small molecules [9][10][11] are typical materials for electrochromic uses.…”
Section: Introductionmentioning
confidence: 99%